A data-driven approach to the development of a supervisory control system for an industrial semi-autogenous grinding circuit - Leon, Revocatus Xolile (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Ing.) -- University of Stellenbosch, 1999.